The Interaction between Legal Representation and Extralegal Factors on Nonviolent Misdemeanor Case Outcomes. (25th July 2022) - Smith, Alisa; Maddan, Sean
Abstract: Several theories propose that extralegal factors influence criminal justice outcomes, particularly in less serious cases. Legal representation is intended to afford defendants, even in less serious cases, due process and fair proceedings. So, legal representation should neutralize the effect of extralegal factors in determining criminal justice outcomes, and this should be the case whether the representation is public or private. This study examined the interactive effect of representation and race on predisposition release at first appearance, pretrial diversion offers, and jail sentences to test this proposition. The results showed that public representation did not improve outcomes for white or nonwhite defendants on their likelihood of release at first appearance or receiving jail sentences. Private representation improved outcomes for white defendants but not nonwhite defendants on offers of pretrial diversion. Possible explanations for and the theoretical implications of these findings and suggestions for future research are discussed.